Tanggapan Atas Pelaksanaan Tugas Account Representative Oleh Wajib Pajak (Survey Pada Kantor Pelayanan Pajak Madya Bandung) - Urip Santoso (SOSIALITA, 2010)
It is an obligation to each citizen to pay tax, however there is a lack of citizens’ awareness about paying taxes. Therefore, government has to make serious efforts to dig up tax revenue possibilities through tax regulations.Because of the environment and business changes, Direktorat Jenderal Pajak believes that it is a necessity to adjust and to improve its organizational structure, especially improvement in human resources, with the existence of account representative. The role of the account representative are to connect, to serve, to advise, and to supervise tax payers to implement rights and obligations of the tax payers so that the tax payers will not experience difficulties or having any disadvantages because of the bureaucracy.It is expected that account representative can increase the obedience of the tax payers to fulfill their obligations.The purpose of this study is to determine the Response for Account Representative (AR) Task Implementation By Taxpayers at Kantor Pelayanan Pajak Madya BandungThis research used several theories, such as obedience theory, account representative theory, and tax theory. Besides these theories, researcher used analysis of maximum-minimum index.The results showed that the task of Account Representative in connection with the execution of tasks, it turns out oversight duties more dominant than other duties, which are for services and coaching. However, in performing its supervisory duties, Account Representative, keep doing good service to the taxpayer. This is performed in order to support their primary task.